Physicochemical and Heavy Metals Characteristics of Soil from Three Major Dumpsites in Ilorin Metrpolis, North Central Nigeria - E. Shehu-Alimi; I. Esosa; B.A. Ganiyu; S. Olanrewaju; O. Daniel (Journal of Applied Sciences and Environmental Management, 2020)
Impact of waste disposal and management is a worldwide phenomenon leading to health impact most especially in underdeveloped and developing world. This study was undertaken to assess the major contaminants in some municipal waste disposal sites and the prospective impact to the surrounding domestic water supply source as well as the impact on the health of the people in the city. This is carried out by studying various physico-chemical parameters of soil which were collected from three municipal dump locations namely; Ita-Amodu, Sawmill garage and Kuntu areas in Ilorin metropolis, Kwara State Nigeria. The geochemistry of the dumpsites were studied with respect to important parameters such as pH, electrical conductivity, temperature, sulphates, chlorides, nitrates, moisture content, organic matter and heavy metals having the following constituents present in its composition- Cadmium (Cd), Lead (Pb), Zinc (Zn), Iron (Fe), and Copper (Cu). The study revealed that the three different soils samples: “(A) Ita-Amodu”, “(B) Sawmill Garage”, and “(C) Kuntu”) have pH of 7.1, 7.2 and 6.8, respectively. Temperature of 24.2, 26.4, and 28.0 oC, Organic matter compositions of 0.95%, 0.73%, and 1.14%. The Moisture contents were 3.93%, 2.89%, and 3.48% respectively. The chloride  contents of the samples was found to be 31.76 mg/L, 48.98 mg/L, and 91.63 mg/L, while nitrates were found to be 0.10 mg/L, 0.06, mg/L and 0.23 mg/L, with a sulphate values of 1.96 mg/L, 2.35 mg/L, and 2.14 mg/L. The conductivities were 1.79 μs/cm, 2.23 μs/cm, and 1.15 μs/cm respectively. Heavy metal analysis from the waste soil were found to contained copper (Cu) - 0.03 mg/L, 0.028 mg/L, and 0.031 mg/L, zinc (Zn) - 0.04, mg/L 0.009 mg/L, and 0.066 mg/L), cadmium (Cd) - 0.516 mg/L, 0.62, mg/L and 0.048 mg/L), Lead (Pb) - 0.063 mg/L, 0.07 mg/L, and 0.056 mg/L), and iron (Fe) - 0.518 mg/L, 0.62 mg/L, and 0.190 mg/L.